Under cover of the night eaudiobook A true story of sex, greed, and murder. - Fanning, Diane (Tantor Media, 2014)
Jocelyn Branham Earnest was found dead on the floor of her living room in Forest, Virginia. By her side was a gun and a suicide note—typed, lacking a signature, and with one fingerprint on it. A fingerprint apparently belonging to Jocelyn's estranged husband. Wesley Earnest was a respected high school administrator, poised to restart his life in a new community. Parents entrusted their children to his care and believed he was above reproach. But the investigation into the life the couple once shared would reveal adultery, troubled finances, and shattered dreams—enough for one man with murder on his mind to travel hundreds of miles.